Utilization of Preventive Measures for Glucocorticoid-Induced Osteoporosis among Veterans with Inflammatory Bowel Disease. (21st April 2013) - Thanou, Aikaterini; Ali, Tauseef; Haq, Omar; Kaitha, Sindhu; Morton, Jordan; Stavrakis, Stavros; Humphrey, Mary Beth
Abstract : Purpose . We examined current osteoporosis prevention practices in patients with inflammatory bowel disease (IBD) on chronic steroid using the 2003 American Gastroenterological Association guidelines as standard of care. Methods . We identified all IBD patients followed at the Oklahoma City VA Medical Center from January 2003 to December 2010, who had been on daily oral steroids (prednisone ≥5 mg or budesonide ≥6 mg) for ≥3 consecutive months. Associations of calcium and vitamin D (vitD) prescribing and bone mineral density (BMD) testing with patient characteristics were examined by logistic regression. Results . Sixty-three of 384 consecutive patients met inclusion criteria. Among 86 steroid courses, calcium and vitD were concurrently prescribed in 46%, and BMD was tested in 30%. There was no association of demographic and clinical characteristics with calcium/vitD prescribing and BMD testing. By multivariate analysis, steroid initiation after 2006, compared to before 2006, was associated with a significant increase in calcium (OR = 3.17 and P = 0.02 ) and vitD (OR = 2.96 and P = 0.02 ) prescribing and BMD testing (OR = 4.63 and P = 0.004 ). Conclusions . We observed a low, yet increasing, adherence to osteoporosis prevention guidelines in IBD since 2003, which highlights the need for continued physician education to enhance guideline awareness and implementation.